2020
DOI: 10.1002/admi.201901983
|View full text |Cite
|
Sign up to set email alerts
|

Micro/Nano Dual‐Scale Crossed Sinusoidal Wavy Patterns for Synergistic Promotion of Proliferation and Endothelial Differentiation of Human Adipose‐Derived Stem Cells

Abstract: Although human adipose‐derived stem cells (hASCs) have great potential as a cell source for stem cell therapy due to their capacity of self‐renewal, long‐term growth, and multipotency with high obtainability through lipoaspiration, little is known about the effects of micro/nano dual‐scale topography on the proliferation and differentiation of the hASCs. In this study, the effects of micro/nano dual‐scale crossed sinusoidal wavy patterns (SIMNs) on the hASC behaviors including cellular alignment, proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…For endothelial and neuronal differentiation, grooves and structured network patterns are used instead of fibers. Shi et al and Kim et al demonstrated that nanogrooves enhance the endothelial differentiation of ASCs [ 119 , 120 ]. In the study of Kim et al, a complex method for generating sinusoidal grooves with different scales that cross each other was described as representing the natural shape of vascular structures.…”
Section: Influence Of Materials Properties On Adipose-derived Stem Ce...mentioning
confidence: 99%
“…For endothelial and neuronal differentiation, grooves and structured network patterns are used instead of fibers. Shi et al and Kim et al demonstrated that nanogrooves enhance the endothelial differentiation of ASCs [ 119 , 120 ]. In the study of Kim et al, a complex method for generating sinusoidal grooves with different scales that cross each other was described as representing the natural shape of vascular structures.…”
Section: Influence Of Materials Properties On Adipose-derived Stem Ce...mentioning
confidence: 99%